Institutional Restructuring to Sustain Regulatory Reform in Indonesia - Wicipto Setiadi (Hasanuddin Law Review, 2019)
There are numerous institutions in Indonesia that form regulations with its exceeding number of regulators may result in poor quality regulations. The outcome leads to regulations being over-regulated, overlapping, disharmony, and conflict. Hence, steps are needed to be taken to overcome in order for more improved and comprehensive regulation in Indonesia. A key factor to overcome poor conditions of regulation in Indonesia is by applying the good regulatory practice. Referring to the practice, there are several standards or principles that can be used as references. Apart from this, taking institutional restructuring into consideration, an establishment of a single institution to form regulations that are strong, full authority to conduct the process of forming regulations. The paper presented is based on literature reviews and documents relating to the subject at hand. From this research, systematic writing was produced using a juridical-analytical approach. This study aims to support the establishment of single-centered Ministry of Laws or Regulation with a strong organizational structure filled with qualified experts and capable professionals.